Switch on tunnel vision: Portable wind tunnels to understand and quantify aeolian processes - Miriam Britt Marzen; Kanat Akshalov; Carlos Asensio Grima; Fernando Avecilla; Daniel E. Buschiazzo; Juan Cruz Colazo; Elisabetta Del Bello; Lars Engelmann; Vicken Etyemezian; Michael Raymond Fischella; Wolfgang Fister; Roger Funk; et al. (Earth-Science Reviews, 2026)

Wind erosion after steppe conversion in Kazakhstan - Moritz Koza; Roger Funk; Julia Pöhlitz; Christopher Conrad; Olga Shibistova; Tobias Meinel; Kanat Akshalov; Gerd Schmidt (Soil and Tillage Research, 2024)

Landscape structure model based estimation of the wind erosion risk in Brandenburg, Germany - Roger Funk; Lidia Völker; Detlef Deumlich (Aeolian Research, 2023)

Low airborne tenacity and spread of ESBL ‐/ AmpC ‐producing Escherichia coli from fertilized soil by wind erosion - Paul Siller; Katrin Daehre; Kerstin Rosen; Steffen Münch; Alexander Bartel; Roger Funk; Ulrich Nübel; Thomas Amon; Uwe Roesler (Environmental Microbiology, 2021)
Summary ESBL‐/AmpC‐producing Escherichia coli from organic fertilizers were previously detected on soil surfaces of arable land and might be emitted by wind erosion. To investigate this potential environmental transmission path, we exposed ESBL‐/AmpC‐positive chicken litter, incorporated in agricultural soils, to different wind velocities in a wind tunnel and took air samples for microbiological analysis. No data exist concerning the airborne tenacity of ESBL‐/AmpC‐producing E . coli . Therefore, we explored the tenacity of two ESBL/AmpC E . coli strains and E . coli K12 in aerosol chamber experiments at different environmental conditions. In the wind tunnel, ESBL/AmpC‐producing E . coli were detected in none of the air samples ( n = 66). Non‐resistant E . coli were qualitatively detected in 40.7% of air samples taken at wind velocities exceeding 7.3 m s −1 . Significantly increased emission of total viable bacteria with increasing wind velocity was observed. In the aerosol chamber trials, recovery rates of airborne E . coli ranged from 0.003% to 2.8%, indicating a low airborne tenacity. Concluding, an emission of ESBL/AmpC E . coli by wind erosion in relevant concentrations appears unlikely because of the low concentration in chicken litter compared with non‐resistant E . coli and their low airborne tenacity, proven in the aerosol chamber trials.

Agricultural fertilization with poultry manure results in persistent environmental contamination with the pathogen Clostridioides difficile - Martinique Frentrup; Nadine Thiel; Vera Junker; Wiebke Behrens; Steffen Münch; Paul Siller; Tina Kabelitz; Matthias Faust; Alexander Indra; Stefanie Baumgartner; Kerstin Schepanski; Thomas Amon; et al. (Environmental Microbiology, 2021)
Summary During a field experiment applying broiler manure for fertilization of agricultural land, we detected viable Clostridioides (also known as Clostridium ) difficile in broiler faeces, manure, dust and fertilized soil. A large diversity of toxigenic C . difficile isolates was recovered, including PCR ribotypes common from human disease. Genomic relatedness of C . difficile isolates from dust and from soil, recovered more than 2 years after fertilization, traced their origins to the specific chicken farm that had delivered the manure. We present evidence of long‐term contamination of agricultural soil with manure‐derived C . difficile and demonstrate the potential for airborne dispersal of C . difficile through dust emissions during manure application. Clostridioides genome sequences virtually identical to those from manure had been recovered from chicken meat and from human infections in previous studies, suggesting broiler‐associated C . difficile are capable of zoonotic transmission.

Using 137Cs to estimate wind erosion and dust deposition on grassland in Inner Mongolia-selection of a reference site and description of the temporal variability - Roger Funk; Yong Li; Carsten Hoffmann; Matthias Reiche; Zhuodong Zhang; Junjie Li; Michael Sommer (Plant and Soil, 2012)

Grazing changes topography-controlled topsoil properties and their interaction on different spatial scales in a semi-arid grassland of Inner Mongolia, P.R. China - Angelika Kölbl; Markus Steffens; Martin Wiesmeier; Carsten Hoffmann; Roger Funk; Julia Krümmelbein; Agnieszka Reszkowska; Ying Zhao; Stephan Peth; Rainer Horn; Marcus Giese; Ingrid Kögel-Knabner (Plant and Soil, 2011)

Molecular Phylogenetic Relationships Among Crested-tailed Mice (Genus Habromys) - Duke S. Rogers; Christopher C. Funk; Jacqueline R. Miller; Mark D. Engstrom (Journal of Mammalian Evolution, 2007)